PENGARUH PERSEPSI RISIKO DAN MOTIVASI INVESTASI TERHADAP KEPUTUSAN INVESTASI MASYARAKAT KOTA BEKASI PADA APLIKASI BIBIT - Shofia Lativatun Nisa; Nurul Hidayah; Dwi Indah (Asosiasi Dosen Muda Indonesia, 2025)
The purpose of this study is to analyze the influence of risk perception and investment motivation on investment decisions of Bekasi City residents on the Bibit application. The analysis method in this study uses quantitative primary data, the test stages carried out are: validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, f test, t test, determination coefficient. The data used in this study used a questionnaire instrument, and valid data that was successfully collected were 100 respondents. The sampling method in this study was non-probability sampling with a purposive sampling technique. The testing tool used was IBM SPSS 30 software.